Healthy Kids Program Improving Children's Nutritional Awareness Through Interactive Learning - Desty Endrawati Subroto; Dadang Muhammad Hasyim; Abiyasa Eka Saputra (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Malnutrition and low nutrition literacy among school-aged children remain significant public health challenges in Indonesia, including in Rangkasbitung, Banten. This community service initiative, the Healthy Kids Program: Improving Children's Nutritional Awareness Through Interactive Learning, aimed to enhance children's understanding of balanced nutrition and foster healthy eating behaviors through engaging, interactive methods. The program employed educational games, simulations, and discussions to encourage active participation, complemented by the involvement of parents and teachers to reinforce learning outcomes at home and in the school environment. A pre-test and post-test were conducted to measure changes in children's knowledge, with results indicating a substantial increase in understanding of balanced nutrition and healthy food choices, rising from an average of 47% to 83%. Additionally, the program provided educational materials to schools, supporting the sustainability of nutrition education initiatives in the community. The findings align with evidence highlighting the effectiveness of interactive and community-based approaches in improving nutrition literacy and promoting healthy dietary practices among children. By building local capacity and aligning with public health goals, the Healthy Kids Program demonstrates its potential as a scalable and replicable model for addressing malnutrition challenges in similar contexts. This initiative underscores the importance of integrating interactive learning with family and community engagement to support the development of healthy lifestyles among school-aged children, contributing to broader efforts to achieve Sustainable Development Goals related to child health and education.